2020
DOI: 10.3390/ijms21228592
|View full text |Cite
|
Sign up to set email alerts
|

Cachexia, a Systemic Disease beyond Muscle Atrophy

Abstract: Cachexia is a complication of dismal prognosis, which often represents the last step of several chronic diseases. For this reason, the comprehension of the molecular drivers of such a condition is crucial for the development of management approaches. Importantly, cachexia is a syndrome affecting various organs, which often results in systemic complications. To date, the majority of the research on cachexia has been focused on skeletal muscle, muscle atrophy being a pivotal cause of weight loss and the major fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 154 publications
1
22
0
7
Order By: Relevance
“…The mechanisms as well as the significance of skeletal muscle wasting and fat loss in cancer cachexia have been identified. However, whether bone metastasis-free tumor growth is associated with bone loss in cancer cachexia remains unclear [ 60 ]. Importantly, muscle loss is associated with bone dysfunction, which reduces mobility and quality of life [ 48 , 60 ] and this association was also found in cancer patients [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms as well as the significance of skeletal muscle wasting and fat loss in cancer cachexia have been identified. However, whether bone metastasis-free tumor growth is associated with bone loss in cancer cachexia remains unclear [ 60 ]. Importantly, muscle loss is associated with bone dysfunction, which reduces mobility and quality of life [ 48 , 60 ] and this association was also found in cancer patients [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, whether bone metastasis-free tumor growth is associated with bone loss in cancer cachexia remains unclear [ 60 ]. Importantly, muscle loss is associated with bone dysfunction, which reduces mobility and quality of life [ 48 , 60 ] and this association was also found in cancer patients [ 61 ]. Therefore, it is important to determine whether tumor growth is associated with the occurrence of bone loss in cancer cachexia and identify mechanisms underlying bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle loss in cachexia is due to both reduced protein synthesis and increased catabolism (proteolysis) due to multiple factors including reduced oral intake, high levels of inflammation, tumor-mediated effects, low physical activity, and endocrine and metabolic disturbances [96]. Some studies have demonstrated that CR can have an effect on the majority of these mechanisms; however, PLA-controlled studies have shown mixed results.…”
Section: Potential Of Creatine Supplementation For Cachexiamentioning
confidence: 99%
“…Hence, to heighten the awareness of conditions potentially inducing cachexia, it is essential to speed up the identification of novel diagnostic markers to improve the diagnosis of cachexia. The onset of cachexia has been proven to occur before evident weight loss and muscle wasting; thus, it is critical to search for adipose-related biomarkers to facilitate early diagnosis and an appropriate therapy response [ 38 ]. It has been suggested that non-coding RNAs, with their conserved structure and stable expression in the cytoplasm, are ideal biomarkers [ 39 ].…”
Section: Discussionmentioning
confidence: 99%